RoboCup 3D Soccer Simulation Server: A Progressing Testbed for AI Researchers - Darab, Mohammad Ali Darvish; Ebrahimi, Mosalam (Applications and Innovations in Intelligent Systems XIV, 2006)
RoboCup 3D Soccer Simulation is a growing domain that makes a wide variety of AI and Multi-Agent researches possible. The RoboCup 3D Soccer Simulation Server is a Multi-Agent environment that supports 22 independent agents to play a soccer match within a real-time and complex environment. Many researchers from all over the world have been using this simulator to pursue their researches in a wide variety of areas such as multiagent learning, cooperative actions and multiagent planning. This paper illustrates the current organization of RoboCup 3D Soccer Simulation Server.